Behavioral responses by an apex predator to urbanization. (2nd March 2019) - Ellington, E Hance; Gehrt, Stanley D
Abstract: Wildlife can respond to urbanization positively (synanthropic) or negatively (misanthropic), and for some species, this is a nonlinear process, whereby low levels of urbanization elicit a positive response, but this response becomes negative at high levels of urbanization. We applied concepts from foraging theory to predict positive and negative behavioral responses of coyotes ( Canis latrans ) along an urbanization gradient in the Chicago metropolitan area, USA. We estimated home range size and complexity, and metrics of 3 movement behaviors (encamped, foraging, and traveling) using Hidden Markov movement models. We found coyotes exhibited negative behavioral responses to highly urbanized landscapes: coyotes viewed the landscape as lower quality, riskier, and more fragmented (home range size and complexity, and time spent encamped increased). Conversely, we found evidence of both positive and negative responses to suburban landscapes: coyotes not only viewed the landscape as higher quality than natural fragments and equally risky, but also viewed it as fragmented (home range size decreased, time spent encamped did not change, and home range complexity increased). Although the spatial and behavioral responses of coyotes to urbanization became increasingly negative as urbanization increased, coyotes were still able to occupy highly urbanized landscapes. Our study demonstrates how wildlife behavioral responses can be dependent on the degree of urbanization and represents one of the first descriptions of apex predator space use and movement in a highly urbanized landscape. Abstract : As urbanization increases globally, wildlife must respond. We applied concepts from foraging behavior to determine how coyote movement behavior varies across a gradient of urbanization. In suburban landscapes, coyotes responded positively by requiring less space to live. In highly urbanized landscapes, coyotes responded negatively by requiring more space and spending more time not moving. Despite these challenges, coyotes can thrive in highly urbanized landscapes, such as downtown Chicago, USA.